Implementasi Model Pembelajaran Project Based Learning Pada Mata Pelajaran Pendidikan Agama Islam - Meiyanda, Rana; Botifar, Maria (Al-Mau'izhoh: Jurnal Pendidikan Agama Islam, 2025)
This study aims to analyze the implementation of the Project Based Learning (PjBL) model in enhancing students’ learning activities in Islamic Religious Education at SMPN 29 Rejang Lebong. This research stems from a gap in the existing literature, namely the limited number of studies that thoroughly explore the planning, implementation, and evaluation processes of PjBL within the context of Islamic Religious Education in a pesantren-based environment, particularly through qualitative approaches that emphasize classroom dynamics. The study employed a qualitative approach using a field-based case study design to obtain a comprehensive understanding of PjBL implementation. Data were collected through observations, in-depth interviews, and documentation. Participants included the school principal, Islamic Religious Education teacher, and 50 students from grades VI, VII, and VIII selected through snowball sampling. Data analysis followed an interactive model by Miles and Huberman, consisting of data reduction, data display, and conclusion drawing, reinforced by source and method triangulation. The findings indicate that in the planning stage, the teacher prepared instructional tools, formulated learning problems, and developed project designs; during implementation, students actively engaged in scheduling, collaborative work, project production, and presentation; while in the evaluation stage, both teacher and students conducted authentic assessments of the work processes and final products. The implementation of PjBL was found to enhance student engagement, creativity, learning responsibility, and problem-solving skills, although challenges such as limited time, varying student abilities, and unequal availability of supporting facilities were identified.